Characterization of Gas Injection Flow Patterns Subject to Gravity and Viscous Forces - Van De Ven, C.J.C (2020)
Gas movement in otherwise water‐saturated porous media is complex and is important for a variety of applications. The interplay of gravity, capillary, and viscous forces influences the movement and resulting pattern of gas. To develop a better understanding of this competition among these forces, air injection experiments were performed in an intermediate‐scale, two‐dimensional flow cell at injection rates of 0.1, 10, 100, 250, and 498 mL min−1. The resulting gas patterns were characterized using gas pressure measurements and optical density measurements based on digital images to classify gas flow as continuous, transitional, or discontinuous, and near‐pore‐scale observations of transient gas flow were made to gain insight concerning the influence of gravity, viscous, and capillary forces. These observations highlighted the importance of gravity and viscous forces, along with capillary forces, for gas flow in water‐wet media. Based on these observations, a simplified dimensionless number (the ratio of the Bond and Capillary numbers) was proposed to quantify the interplay of gravity to viscous forces, and its validity for the prediction of the type of gas flow was assessed. This study provides a high spatiotemporal dataset of transient gas movement in homogeneous sand, which can be used to provide insight for multiphase flow modeling efforts and future understanding of gas movement coupled to mass transfer.